2021
DOI: 10.1007/978-3-030-63549-7_13
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Respiratory Infection

Abstract: Respiratory infections are an important and frequent cause of morbidity and mortality globally. Sex and gender-based differences in lung infection are recognized and gradually gaining importance due to the potential for gender-tailored therapeutics. While sex and gender differences are widely acknowledged in the evaluation of chronic respiratory disease states such as asthma, chronic obstructive pulmonary disease (COPD), and cystic fibrosis (CF), acute and chronic respiratory infection complicate all of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 237 publications
(292 reference statements)
0
2
0
Order By: Relevance
“…Being female gendered seems to be a protective factor in line with prior studies. The reason for this gender difference in ARI symptoms seems to be differences in lung structure and function between the genders, in that males have larger lungs and females attain an earlier maturity and long-term airway patency compared to their male counterparts [ 20 ]. In addition, children born at a low birth weight [ 33 ] and those who were younger [ 34 ], both had a higher risk of ARI symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being female gendered seems to be a protective factor in line with prior studies. The reason for this gender difference in ARI symptoms seems to be differences in lung structure and function between the genders, in that males have larger lungs and females attain an earlier maturity and long-term airway patency compared to their male counterparts [ 20 ]. In addition, children born at a low birth weight [ 33 ] and those who were younger [ 34 ], both had a higher risk of ARI symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the present study specifies social determinants at multiple levels; these include community-level characteristics, such as community education and community migration status, as well as household-level characteristics, namely maternal education, household poverty, household indoor cooking, household migration and residence. In addition to child’s characteristics, prior studies also suggested gender contingency, in which being female gendered may result in exposure to different risks due to biosocial factors [ 20 ]. The SES vulnerability of these children is hypothesized to increase the risk of ARI symptoms, but this has been studied only rarely in Pakistan.…”
Section: Introductionmentioning
confidence: 99%